RURAL ECONOMIC DEVELOPMENT STRATEGY THROUGH STRENGTHENING RESOURCES POTENTIAL - Meida Rachmawati (Journal of Social Sustainability Management, 2023)
Village development has a significant tendency to be handled uniformly by the central government throughout the New Order era. The village development program is more of a top-down nature. Village development has increasingly been delegated to the community throughout the reform era. Central and local governments assume the position and function of a facilitator, offering financial support, mentoring, and supervision. Many initiatives to reduce poverty have been carried out, including the Assistance Program for Disadvantaged Communities and Education for the President of Disadvantaged Villages. Village development programs are more bottom-up or a mixture of bottom-up and top-down. The research is included in qualitative research, namely research that does not use mathematical calculations, statistics, and so on, but uses scientific emphasis or findings that cannot be achieved using statistical procedures or another quantified method. In prodding financial development, monetary strategy should stick to another worldview in which individuals' monetary strengthening should be the worry in light of the fact that the vast majority in rustic regions live in the horticultural area, it actually makes a huge commitment to the territorial economy, enabling individuals' economy likewise implies fabricating a superior country economy. Modern advancement should focus on the retrogressive linkage with the farming area or the essential area, while the forward linkage should focus on handling to increment added worth and great promoting so the items delivered are not squandered.